ANALISIS PRODUKTIVITAS DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) SEBAGAI DASAR PERBAIKAN PADA MESIN PENGOLAHAN BIJI PLASTIK DI PT. X - Novita Nouryend, (2021)
PT.X is a manufacturing company that produces LDPE and HDPE plastics. The problem that occurs is that the corrective maintenance activities carried out by PT.X machines are considered inaccurate because of continuous production delays or in the sense that the machine's effectiveness is low. Based on these problems, the OEE method is used to determine the effectiveness of machine performance, then look for the relationship between the variables and the OEE value as well as the dominant factors of the independent variables that affect the OEE value. After that FMEA to identify the highest causes of failure and cause and effect diagrams to find the basic factors for the emergence of these problems as a basis for providing recommendations for improvement. The results showed that the OEE value was 59.79%, which means it is still below the world standard. All variables affect the OEE value, the variable that has the biggest influence on the low OEE value is downtime due to high machine set-up time with an RPN value of 60. The root of the problem is the operator is less competent, the machine is old, there is no scheduled repair and temperature. in a high work environment. The proposal given was to provide periodic training, schedule repairs and engine checks, and update space for better air circulation.